Serum complement component 3, complement component 4 and complement component 1q levels predict progressive visual field loss in older women with primary angle closure glaucoma - Li, Shengjie; Qiu, Yichao; Yu, Jian; Shao, Mingxi; Li, Yingzhu; Cao, Wenjun; Sun, Xinghuai (British journal of ophthalmology, 2023)
AimTo evaluate the association between serum levels of complement component (C) 3, C4 and C1q and visual field (VF) loss in patients with primary angle closure glaucoma (PACG).MethodsIn this prospective cohort study, a total of 308 patients with PACG were included. The patients were followed up every 6 months (at least 2 years), with clinical examination and VF testing. Based on their sex and age, the subjects were stratified into male and female subgroups, and by age at <60 and ≥60 years per subgroup.ResultsOne hundred twenty-three (39.94%) patients showed glaucoma VF progression. The serum levels of C3, C4 and C1q were significantly lower (p<0.05) in the progression group compared with the non-progression group in the ≥60 years female subgroup. In female patients with age ≥60 years, (1) lower levels of baseline C3 (HR=0.98, p<0.001), C4 (HR=0.96, p=0.01) and C1q levels (HR=0.99, p=0.003) were associated with a greater risk of VF progression; (2) patients with lower C3 levels had significantly (p<0.05) higher rates of VF loss progression, similar to those with lower C4 and lower C1q levels; and (3) the generalised additive model revealed a negative correlation between baseline C3 (p<0.001), C4 (p<0.001) and C1q (p<0.001) levels with the risk of VF progression. No statistical significance was observed in the male (<60 and ≥60 years) and female (<60 years) subgroups.ConclusionDecreased C3, C4 and C1q levels at baseline were significantly associated with a greater risk of VF loss progression only in older women with PACG.